Transition metal ions at the crossroads of mucosal immunity and microbial pathogenesis - Diaz-Ochoa, Vladimir; Jellbauer, Stefan; Klaus, Suzi; Raffatellu, Manuela (Frontiers in Cellular and Infection Microbiology, 2014)
Transition metal ions are essential micronutrients for all living organisms. In mammals, these ions are often protein-bound and sequestered within cells, limiting their availability to microbes. Moreover, in response to infection, mammalian hosts further reduce the availability of metal nutrients by activating epithelial cells and recruiting neutrophils, both of which release metal-binding proteins with antimicrobial function. Microorganisms, in turn, have evolved sophisticated systems to overcome these limitations and acquire the metal ions essential for their growth. Here we review some of the mechanisms employed by the host and by pathogenic microorganisms to compete for transition metal ions, with a discussion of how evading “nutritional immunity” benefits pathogens. Furthermore, we provide new insights on the mechanisms of host-microbe competition for metal ions in the mucosa, particularly in the inflamed gut.